Autobiographical memory in chronic schizophrenia: a follow-up study - Herold, Christina; Duval, Céline Z.; Schröder, Johannes (Neuropsychologia, 2023)
Chronic schizophrenia is a very disabling disease and patient’s social integration remains difficult. One important aspect is autobiographical memory (AM) as it is impaired in schizophrenia and highly correlated to patient’s outcome, since its closely linked to self and identity. Reduced specificity and lack of details are characteristics of patients′ AM, but its longitudinal course in schizophrenia remains unclear. We examined 21 patients who underwent our protocol twice with an interval of 7 years. AM was assessed using a semi-structured interview, covering four periods of life and addressing semantic knowledge and autobiographical episodes as well as their details. The results can be divided into three parts, separating semantic memories, specific autobiographical memories and details describing the latter. While a significant deterioration of semantic AM over time could be revealed, the specificity of the free recalled autobiographical episodes remained rather stable - albeit on a low level. In contrast, unique events were remembered with significantly less details at follow-up than at the first examination. While floor-effects given a relatively small number of unique events have to be considered, semantic AM and episodic details seem to be a valuable target for AM remediation given their further deterioration over time.